Retinoid signaling regulates angiogenesis and blood‐retinal barrier integrity in neonatal mouse retina. (5th March 2022) - Engelbrecht, Eric; Metzler, Melissa A.; Sandell, Lisa L.
Abstract: Objective: The neonatal mouse retina is a well‐characterized experimental model for investigating factors impacting retinal angiogenesis and inner blood‐retinal barrier (BRB) integrity. Retinoic acid (RA) is an essential signaling molecule. RA is needed for vasculogenic development in embryos and endothelial barrier integrity in zebrafish retina and adult mouse brain; however, the function of this signaling molecule in developing mammalian retinal vasculature remains unknown. This study aims to investigate the role of RA signaling in angiogenesis and inner BRB integrity in mouse neonatal retina. Methods: RA distribution in the developing neurovascular retina was assessed in mice carrying an RA‐responsive transgene. RA function in retinal angiogenesis was determined by treating C57BL/6 neonatal pups with a pharmacological inhibitor of RA signaling BMS493 or control vehicle. BRB integrity assessed by monitoring leakage of injected tracer into extravascular retinal tissue. Results: RA signaling activity is present in peripheral astrocytes in domains corresponding to RA activity of the underlying neural retina. RA inhibition impaired retinal angiogenesis and reduced endothelial cell proliferation. RA inhibition also compromised BRB integrity. Vascular leakage was not associated with altered expression of CLDN5, PLVAP, LEF1, or VEcad. Conclusions: RA signaling is needed for angiogenesis and integrity of the BRB in the neonatal mouse retina.